Transcriptional up-regulation of genes involved in photosynthesis of the Zn/Cd hyperaccumulator Sedum alfredii in response to zinc and cadmium. (December 2016) - Tang, Lu; Yao, Aijun; Ming Yuan,; Tang, Yetao; Liu, Jian; Liu, Xi; Qiu, Rongliang
Abstract: Zinc (Zn) and cadmium (Cd) are two closely related chemical elements with very different biological roles in photosynthesis. Zinc plays unique biochemical functions in photosynthesis. Previous studies suggested that in some Zn/Cd hyperaccumulators, many steps in photosynthesis may be Cd tolerant or even Cd stimulated. Using RNA-seq data, we found not only that Cd and Zn both up-regulated the CA1 gene, which encodes a β class carbonic anhydrase (CA) in chloroplasts, but that a large number of other Zn up-regulated genes in the photosynthetic pathway were also significantly up-regulated by Cd in leaves of the Zn/Cd hyperaccumulator Sedum alfredii . These genes also include chloroplast genes involved in transcription and translation (rps18 and rps14), electron transport and ATP synthesis (atpF and ccsA), Photosystem II (PSBI, PSBM, PSBK, PSBZ/YCF9, PSBO-1, PSBQ, LHCB1.1, LHCB1.4, LHCB2.1, LHCB4.3 and LHCB6) and Photosystem I (PSAE-1, PSAF, PSAH2, LHCA1 and LHCA4). Cadmium and Zn also up-regulated the VAR1 gene, which encodes the ATP-dependent zinc metalloprotease FTSH 5 (a member of the FtsH family), and the DAG gene, which influences chloroplast differentiation and plastid development, and the CP29 gene, which supports RNA processing in chloroplasts and has a potential role in signal-dependent co-regulation of chloroplast genes. Further morphological parameters (dry biomass, cross-sectional thickness, chloroplast size, chlorophyll content) and chlorophyll fluorescence parameters confirmed that leaf photosynthesis of S. alfredii responded to Cd much as it did to Zn, which will contribute to our understanding of the positive effects of Zn and Cd on growth of this plant. Graphical abstract: Highlights: Zn/Cd up-regulated photosynthesis-related genes in hyperaccumulator Sedum alfredii. Zn/Cd supported better morphological parameters and growth of S. alfredii leaves. Leaf chlorophyll fluorescence parameters responded to Cd much as it did to Zn.